Parental view of epilepsy in Angelman syndrome: a questionnaire study. Issue 5 (1st November 1998) - Ruggieri, M; McShane, M A
Abstract : PURPOSE: To explore parents' opinions and concerns about seizures, anticonvulsants, and the effect of treatment in children with Angelman syndrome. DESIGN: A postal questionnaire was sent to members of one of the UK lay groups for Angelman syndrome (ASSERT) who had a child affected by Angelman syndrome. The questionnaire requested general medical information and information about the epilepsy, its treatment, and treatment responses. RESULTS: One hundred and fifty questionnaires were sent out with an ASSERT routine mailing and 78 completed questionnaires were returned. Forty three patients were boys and 35 were girls; ages ranged from 1.7 to 25 years (mean 7.5 years). The overall general clinical and cytogenetic data were mostly consistent with previous reports. Epilepsy was reported in 68 children, most of whom had a detectable cytogenetic deletion. The most common seizure types reported by the families were absence seizures, tonic clonic seizures, drop attacks, and myoclonic seizures; in four patients only febrile seizures occurred. The age at onset of the seizures was < 2 years in more than half of the patients. Anti-epileptic drug treatment with valproate (VPA), clonazepam (CZP), and lamotrigine (LTG) as monotherapy or a combination of VPA and CZP or VPA and LTG was more often viewed favourably and considered effective with fewer side effects on the child's behaviour and alertness, versus more frequent adverse effects and increased frequency and severity of seizures with carbamazepine (CBZ) and vigabatrin (VGB) in monotherapy or in combination with other anti-epileptic drugs. Seizures did tend to improve with age but were still present and disabling at older ages. CONCLUSIONS: This is the first study to record parents' opinions about seizures, anti-epileptic drugs, and treatment responses in children with Angelman syndrome, and it is one of the largest series on epilepsy and Angelman syndrome to be reported to date.